Small bowel metastasis from pancreatic cancer in a long-term survival patient with synchronous advanced malignant pleural mesothelioma: A case report and literature review - Fasano, Morena (Oncol Lett, 2016)
Diffuse malignant pleural mesothelioma (MPM) is an aggressive tumor that originates from the surface of the pleura. Approximately 70% of cases are associated with chronic asbestos exposure. MPM is regarded as an incurable disease, with a median survival of ~2 years following intensive multimodality treatment. Pancreatic cancer is a malignancy also associated with a poor prognosis, with only 2% of patients surviving for 5 years. The majority of patients with pancreatic cancer are diagnosed with an advanced stage of disease and experience a poor response to therapy. The development of synchronous MPM and other types of cancer is rare. The present study describes a patient with synchronous, biphasic MPM and pancreatic adenocarcinoma, who was treated with a multimodal therapeutic approach with stereotactic body radiation therapy. Due to a suspected diagnosis of ‘acute abdomen’, an emergency small intestine resection was performed and a subsequent diagnosis of moderately-differentiated adenocarcinoma was confirmed. During a further immunohistochemical examination, pathologists determined that the small bowel metastasis descended from pancreatic cancer. The onset of bowel metastasis is an event rarely associated with MPM, and has not been previously described in the literature for cases of pancreatic cancer. Therefore, to the best of our knowledge, the present study describes the first case of intestinal metastasis from pancreatic cancer in a long-term survival patient with biphasic MPM.